Parametric method of normalization and training architects in modern conditions - Омельяненко, Максим Вікторович; Омельяненко, Марина Вікторівна (Theory and practice of design, 2021)
This article aims to define, using the parametric normalization method, the main areas of reviewing approaches to the development of basic knowledge of future architects able to solve issues of designing architectural projects of different levels of complexity on their own after graduation. In today’s context of increasing intensification of manufacturing processes and establishment of new objects when consumer demands for living environment and activities change all the time, new materials and technologies are extensively adopted, the relevant matter includes efficient training of future architects able to independently solve issues related to the establishment of new construction objects after graduation, formation of the internal and external environment given the current filed requirements. One of the crucial problems is the architect’s ability to perform project tasks based on knowledge of the functional object structure, requirements of potential customers, taking into account particularities of object placement in the chosen territory, simultaneously creating a safe, reliable and comfortable environment that can implement functions it is designed for. It is these positions that architects should rely on while starting working on the project, and the higher education institution should train them for such activity as good as possible. Statutory support of the construction industry should not dictate a project solution to architects. It should allow selecting the best possible option among several ones while architects make an ultimate decision. This is one of the fundamental principles of the parametric normalization method in the construction industry, which is now implemented in Ukraine. It is the serious reformation of the field’s statutory framework, and future architects should be ready for this aspect.